Modeling the exchange rate using price levels and country risk - Gábor Reg\~os (Cogent Economics & Finance, 2015)
This paper builds two factor discrete time models in order to investigate the effect of sovereign risk on the nominal exchange rates in a Markov switching framework. The empirical section of the paper uses seven currencies from Chile, the Czech Republic, Hungary, Iceland, Japan, Korea, and Mexico. To measure the sovereign risk, we use the credit rating agencies' ratings classes as proxy variable. In the empirical part, four different versions of the model are calibrated and their in-sample and out-of-sample data will be analyzed leading to the conclusion that none of the four versions dominates the others. As an additional result, it is revealed that risk has significant effect on the nominal exchange rates.
Keywords: C15; C33; C53; F31; 330; exchange rate; multifactor model; ratings classes; Markov-switching model